Analisis Pertumbuhan Kinerja Keuangan PT Bank Mandiri (Persero) Tbk - Hidayatullah, Hidayatullah (Bina Nusantara University, 2011)
This research was made with a view to assess and analyze financial performance of PT Bank Mandiri Tbk. The assessment was conducted by looking at the financial ratios of from 2003 until 2010, from the financial statements obtained from the website of Indonesian stock exchange, the value of the components of financial statements conducted re-calculation formula into the valuation ratios of the banking financial performance, then the results of are analysed per year. Conclusions from this analysis is compared with indicators of banking health assessment released by Bank Indonesia. Analysed financial ratios taken are among others CAR, NPL, ROA, and ROE. These are commonly used ratios by researchers in assessing the financial performance of banks